2019
DOI: 10.1186/s42501-019-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Coupling textural and stable-isotope variations in fluvial stromatolites: Comparison of Pleistocene and recent records in NE Spain

Abstract: Textural and stable isotopic features of two middle Pleistocene fluvial stromatolite profiles are compared to a recent stromatolite, both formed in the River Piedra system (NE Spain), to test the reliability of climatic, hydrologic and depositional information derived from ancient records. The Pleistocene stromatolites formed in a multi-domed, highly-inclined cascade-barrage. The recent stromatolite also formed in a highly-inclined cascade of the River Piedra, the sedimentary conditions of which were periodica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…However, there is not a perfect match. The 7–8.1°C difference calculated between the large‐crystal and the small‐crystal laminae of the fossil stromatolites is larger than the present difference between summer and winter water temperatures, partially because the large‐crystal laminae represent only the coldest record, while the small‐crystal laminae represent a longer time span (Arenas et al, 2019). Regardless of this difference, the results are satisfactory and significant enough to interpret similar cyclic variations in the same terms in other laminated microbial records.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…However, there is not a perfect match. The 7–8.1°C difference calculated between the large‐crystal and the small‐crystal laminae of the fossil stromatolites is larger than the present difference between summer and winter water temperatures, partially because the large‐crystal laminae represent only the coldest record, while the small‐crystal laminae represent a longer time span (Arenas et al, 2019). Regardless of this difference, the results are satisfactory and significant enough to interpret similar cyclic variations in the same terms in other laminated microbial records.…”
Section: Discussionmentioning
confidence: 72%
“…The textural and isotopic comparison of Pleistocene and recent stromatolites in the River Piedra showed a consistent cyclic pattern in both cases and demonstrated that each lamina couplet corresponds to 1 year (Arenas et al, 2019). The large‐crystal laminae in the fossil stromatolites are comparable to the macrocrystalline laminae that occur in the cool‐period deposits of the recent stromatolites, and the small‐crystal laminae in the fossil specimens are comparable to the warm‐period deposits of the recent stromatolites.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations